Impacts of different environmental factors on tunnelling behaviour of the subterranean termite Odontotermes formosanus (Shiraki). Issue 3 (4th May 2019) - Xu, Huan; Zhu, Qiankun; Hu, Wei; Kim, Kilnam; Lei, Chaoliang; Xiang, Yahong; Huang, Qiuying
Abstract : The subterranean termite Odontotermes formosanus (Shiraki) is one of the most serious pests of dikes and dams in China, and can build large subterranean cavities inside earthen dikes and dams through workers' tunnelling behaviour. For a better understanding of underground tunnelling strategies of O. formosanus, we used the tunnelling device to investigate the effect of substrate type, moisture content and ambient temperature on tunnelling behaviour. We found that the workers displayed significantly higher-tunnelling efficiency and bigger maximum tunnelling distance in sandy soil when compared to soil and sand. Meanwhile, the workers expressed significantly higher-tunnelling efficiency and bigger maximum tunnelling distance under 20% moisture content than those under 10% and 15% moisture contents. Additionally, the workers exhibited significantly higher tunnelling efficiency and bigger maximum tunnelling distance at 28 °C as compared to 22 and 25 °C. These findings suggest that the above three environmental factors had the significant impacts on tunnelling behaviour of the subterranean termite O. formosanus .